2022
DOI: 10.3389/fendo.2022.907249
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing hormone supplementation in women with hypogonadotropic hypogonadism seeking fertility care: Insights from a narrative review

Abstract: The management of infertile women affected by hypogonadotropic hypogonadism (HH) or conditions mimicking it is particularly challenging. In the present narrative review, we aimed to synthesize the available evidence on the benefit (if any) of exogenous luteinizing hormone (LH) supplementation in this group of patients. Available data support LH supplementation in women with organic or functional HH. On the contrary, the benefit of exogenous LH on reproductive outcomes both in advanced maternal age patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 69 publications
0
0
0
Order By: Relevance
“…They reviewed 164 cycles and found that those with lower basal LH levels showed higher fertilization rates and a greater number of fresh embryo transfers (7). Furthermore, Wang et al ( 14) observed significant differences in cumulative clinical pregnancy rates (15). However, there is a balance to be maintained, as excessive LH activity can lead to premature follicular maturation and atresia.…”
Section: Discussionmentioning
confidence: 99%
“…They reviewed 164 cycles and found that those with lower basal LH levels showed higher fertilization rates and a greater number of fresh embryo transfers (7). Furthermore, Wang et al ( 14) observed significant differences in cumulative clinical pregnancy rates (15). However, there is a balance to be maintained, as excessive LH activity can lead to premature follicular maturation and atresia.…”
Section: Discussionmentioning
confidence: 99%